Perceived needs for mental health care and barriers to treatment across age groups. (3rd October 2017) - Forbes, M.K.; Crome, E.; Sunderland, M.; Wuthrich, V.M.
ABSTRACT: Purpose: This study aimed to assess responses to a structured measure of perceived need for treatment to understand whether differences in treatment uptake across age groups are related to differences in: (1) perceived need for mental health care; (2) perceptions of treatment needs being met; and/or (3) perceived attitudinal and structural treatment barriers. Methods: Data from a nationally representative sample of the Australian population (2007 National Survey of Mental Health and Wellbeing) were analysed using logistic and multinomial regression. All participants potentially benefiting from mental health services were included in analyses; including those reporting symptoms of mental disorders, using mental health services, or self-reporting significant mental health problems in the past 12 months ( n = 5733). All regression analyses were adjusted for gender, the presence of chronic physical health conditions, disorder type, and disorder severity. Results: Older adults were the least likely to report any perceived need for mental health care, and specifically reported lower needs for psychotherapy, information about available services, and support improving their ability to work. Older adults perceiving a need for mental health care were also the most likely to report having these needs met. There were no differences in attitudinal and structural barriers to treatment across age groups. Conclusions: These results highlight that age needs to be considered in strategies for improving engagement and efficacy of mental health services, as well as the need for further research to understand what drives age differences in perceived need for mental health care.